Measuring the Generosity of Parental Leave Policies - Otto, Adeline (Social Inclusion, 2021)
In order to investigate and compare welfare states or specific welfare programmes, scientists, opinion‐makers and politicians rely on indicators. As many of the concepts or objects studied are somewhat abstract, these indicators can often only be approximations. In comparative welfare‐state research, scholars have suggested several approximating indicators to quantitatively measure and compare the generosity of public welfare provision, with a special focus on cash benefits. These indicators include social spending, social rights and benefit receipt. We present these indicators systematically, and critically discuss how suitable they are for comparing the generosity of parenting leave policies in developed welfare states. Subsequently, we illustrate how the operationalisation of leave generosity by means of different indicators can lead to different rankings, interpretations and qualifications of countries. Hence, indicator choices have to be considered carefully and suitably justified, depending on the actual research interest.